2006
DOI: 10.1111/j.1743-6109.2006.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Open-Label, Fixed-Dose, Crossover Study to Establish Preference of Patients with Erectile Dysfunction After Taking the Three PDE-5 Inhibitors

Abstract: Introduction We conducted a prospective, randomized, open-label, fixed-dose preference study, with a crossover design, using sildenafil, vardenafil, and tadalafil. Aim To assess patient preference for sildenafil (100 mg), vardenafil (20 mg), and tadalafil (20 mg) for the treatment of erectile dysfunction. Secondary objectives included finding out whether patients would follow treatment with a second or third option, in the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 39 publications
5
30
0
2
Order By: Relevance
“…En el análisis por tratamientos, Sildenafilo presentó valoraciones más positivas que Tadalafilo y Vardenafilo. Estos resultados difieren de los observados por otros autores 27 quizás debido a la propia naturaleza del estudio y el momento en el que fue llevado a cabo. Se podría decir que nuestros resultados se aproximarían más a la realidad clínica al corresponder a un estudio observacional, no intervencionista, realizado en una amplia muestra de pacientes.…”
Section: Discussionunclassified
“…En el análisis por tratamientos, Sildenafilo presentó valoraciones más positivas que Tadalafilo y Vardenafilo. Estos resultados difieren de los observados por otros autores 27 quizás debido a la propia naturaleza del estudio y el momento en el que fue llevado a cabo. Se podría decir que nuestros resultados se aproximarían más a la realidad clínica al corresponder a un estudio observacional, no intervencionista, realizado en una amplia muestra de pacientes.…”
Section: Discussionunclassified
“…Unfortunately, young men with ED are usually assigned a diagnosis of primary psychogenic pathophysiology and not referred to specialists for vascular testing. Thus, young men are often encouraged to undergo long-term, if not life-long, conservative treatment strategies without a thorough, organically focused investigation to help determine potential vasculogenic contributions to the overall ED cause [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that improving erectile function may be an important factor in the sexual experience and an individual's overall satisfaction in their personal life. Yet, while highly effective oral drugs for improving erection hardness have been available for many years, 15 in this study only a small proportion of men (8%) were found to be using such drugs to improve their erection, sexual experience, sexual satisfaction and overall happiness in life.…”
Section: Discussionmentioning
confidence: 82%